Le Djérid, le Souf et le nord de l’Ifrīqiya - Mourad Araar (Revue des Mondes Musulmans et de la Méditerranée)
Located south of Ifrīqiya and straddling the Algerian/Tunisian border, Djerid (Bilād al-Jarīd) and the Suf are contiguous provinces that form a geographical unit with shared natural features. Despite the region’s eccentricity, the importance of economic exchanges and cultural contacts between this region and northern Ifrīqiya, particularly the Tunisian High Steppes, is explained by its geographical location at a crossroads and by the development of inter-regional family relations. The use of written sources and oral traditions reveals a continuity of exchanges and contacts during the Middle Ages and Modern Times, and even after the colonial rise of the 19th century. To understand this question, our interest will focus on three types of exchanges : commercial and pastoral contacts, cultural and social contacts.